Mayotte se prépare au risque tsunami : modélisations, alerte, évacuation, sensibilisation - Frédéric Leone; Monique Gherardi; Matthieu Péroche; Émilie Lagahé; Pierre Aumond; Jonathan Siliezar Montoya; Fahad Idaroussi Tsima; Pablo Poulain; Anne Le Friant; Anne Mangeney; Said Hachim Mogne; Valentin Roudier (EchoGéo)
The French ultra-marine territories are almost all concerned by the tsunami risk. Mayotte does not escape this major hazard, and the risks induced by important issues located on its coastline. Since 2018, due to the seismo-volcanic activity related to the appearance of a new submarine volcano (Mont Fani Maoré), several tsunami simulations have been produced on Mayotte. These models have been used to develop evacuation plans validated by the authorities. Evacuation and warning capacities could be evaluated and discussed, by modeling both the time needed to safe the population and the theoretical audibility of sirens. Mayotte is thus committed to tsunami risk management but the preparation of populations must remain a priority in order to reduce evacuation times despite the difficulties inherent in any new prevention strategy.